1983
DOI: 10.1007/bf01317037
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous mechanisms on exocrine pancreatic secretion initiated by alcohol in the conscious dog

Abstract: Modifications of pancreatic secretion induced by the infusion of alcohol were investigated in seven Thomas fistula dogs. Acute intravenous injections of low doses of alcohol induced a significant increase of all parameters of pancreatic secretion. On the contrary the acute intravenous injection of high doses of alcohol induced a significant decrease of pancreatic secretion. A prolonged-alcohol intravenous infusion producing a stable blood alcohol level provoked at first a decrease of pancreatic secretion, sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
1

Year Published

1984
1984
1991
1991

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…It had already been shown that the vagally mediated inhibition due to intravenous alcohol injection disap peared in chronic alcoholic dogs and was reversed to a strong stimulation of protein and to a lesser extent of water and bicarbon ate secretion [6], This can be explained in the light of recent experiments [22]: in nonalco holic dogs, intravenous ethanol is responsible for two opposite mechanisms, namely inhibi tion and stimulation of pancreatic secretion. Both are abolished by atropine, ganglion blockers and vagotomy, but stimulation is sensitive to much lower alcohol blood levels than inhibition.…”
Section: Discussionmentioning
confidence: 97%
“…It had already been shown that the vagally mediated inhibition due to intravenous alcohol injection disap peared in chronic alcoholic dogs and was reversed to a strong stimulation of protein and to a lesser extent of water and bicarbon ate secretion [6], This can be explained in the light of recent experiments [22]: in nonalco holic dogs, intravenous ethanol is responsible for two opposite mechanisms, namely inhibi tion and stimulation of pancreatic secretion. Both are abolished by atropine, ganglion blockers and vagotomy, but stimulation is sensitive to much lower alcohol blood levels than inhibition.…”
Section: Discussionmentioning
confidence: 97%
“…Under these conditions, there remains a muscarinic stim ulatory mechanism which is localized in the intrapancreatic deuteroneuronc of the vagus or in the acinar cell itself. This could lead to an increased release of acetylcholine in the pancreas responsible for an increased (pro tein) secretion [22], …”
Section: Action Of Alcohol On the Pancreasmentioning
confidence: 99%
“…There are also contrasting reports that pancreatic exocrine secretion is suppressed (Dreiling et al 1952;Tiscornia et al 1973), and stimulated (Walton et al 1962) by intravenous administration of ethanol. Noel-Jorand and Sarles (1983) reported that suppressive and stimulative effects exist in accordance with high and low blood ethanol concentration.However, there appeared to be no reports of studies that have continuously measured variations of the duodenal luminal pH in response to gastrointestinal administration of ethanol. In our study, we simultaneously measured duodenal lumen pH and pancreatic exocrine secretion to determine the effects of gastrointes-…”
mentioning
confidence: 99%
“…There are also contrasting reports that pancreatic exocrine secretion is suppressed (Dreiling et al 1952;Tiscornia et al 1973), and stimulated (Walton et al 1962) by intravenous administration of ethanol. Noel-Jorand and Sarles (1983) reported that suppressive and stimulative effects exist in accordance with high and low blood ethanol concentration.…”
mentioning
confidence: 99%